Deviance in International Relations
XII, 215 p.
Keywords: Rogue states' have been high on the policy agenda for many years but their theoretical significance for international relations has remained poorly understood. In contrast to the bulk of writings on 'rogue states' that address them merely as a policy challenge, this book studies what we can learn from deviance about international politics.